A Novel Production Of Single-Walled Carbon Nanotubes And Hydrogen Via Single-Step Conversion Of Natural Gas. - Mohamed, Prof. Dr. Abdul Rahman; Sharif Zein, Dr. Sharif Hussein; Chai, Dr. ,Siang Pio; lsmail, Assoc. Prof. Dr. Jamil; Miura, Prof. Dr. Kouichi; Equchi, Prof. Dr. Koichi (Universiti Sains Malaysia, 2008)

(untitled)
A number of catalysts prepared from transition metals such as copper (Cu), iron (Fe), nickel (Ni), cobalt (Co) and manganese (Mn) on TiO2 support were tested for the decomposition of methane into hydrogen and carbon.